Pelatihan Penyusunan Artikel Ilmiah Bagi Mahasiswa Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan - Kholili Hasib; Nurhanifansyah Nurhanifansyah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The low level of scientific writing culture among students poses a serious challenge in academia, particularly in the digital era marked by rampant plagiarism and a declining motivation for critical thinking. To address this issue, the Islamic Education Study Program at Universitas Islam Internasional Darullughah Wadda’wah Bangil Pasuruan initiated a scientific article writing training aimed at equipping students with writing skills in accordance with methodological principles and national or international publication standards. The program was carried out in three main phases: preparation, implementation, and evaluation, using a combination of presentation, demonstration, and hands-on practice methods. The integration of supporting applications such as Zotero and Mendeley enhanced the technical aspects of writing. The results of the training indicated a significant improvement in students' understanding and skills in writing scientific articles, as well as an increased interest in publication. An intensive mentoring phase further facilitated the completion of publishable academic works, contributing positively to the institution’s academic reputation. This program has proven effective and should be replicated to foster a strong scientific culture within higher education institutions.